PENGARUH UKURAN PERUSAHAAN, INVESTMENT OPPORTUNITY SET, PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN SEKTOR TRANSPORTATION AND LOGISTICS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Rodiana Lubis; Nora Susanti; Rohmat Suprapto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of company size, investment opportunity set (IOS), profitability, and liquidity on the value of companies in the transportation and logistics sector listed on the Indonesia Stock Exchange for the 2019–2023 period. The phenomenon of fluctuations in company value in this sector creates a research gap, because several previous studies have shown inconsistent results regarding the factors that influence company value. This study uses a quantitative approach with secondary data in the form of annual financial reports of 11 companies selected through purposive sampling with a total of 55 observations. Data analysis was conducted using a panel data regression method using the Random Effect Model approach, as well as partial tests (t-test), simultaneous tests (F-test), and coefficient of determination (R²). The results show that partially, profitability has a significant positive effect on company value at a significance level of 10%, while company size, IOS, and liquidity have no significant effect. Simultaneously, the four independent variables have a significant effect on company value, but with a relatively small contribution of 13%, so that other factors outside the model are more dominant in influencing company value. These findings underscore the importance of profitability as a primary consideration for investors in assessing a company's prospects, while size, investment opportunity set, and liquidity have yet to exert a significant influence.